Does piracy lead to product abandonment or stimulate new product development?: Evidence from mobile platform‐based developer firms - Miric, Milan; Jeppesen, Lars Bo (Strategic Management Journal, 2020)
Research Summary With the growth of digital platforms, understanding the role of property rights on those platforms has become increasingly important. Digital piracy, the unauthorized copying and distribution of digital products, is therefore an important strategic issue, both because of lost revenues and because it is thought to decrease innovation. Yet, while the latter effect is often argued, empirical evidence is limited. We study whether piracy affects innovation and whether it leads firms to shift to different types of innovations. By studying a large piracy event in a mobile app marketplace, we find that piracy leads to a decrease in the release of incremental innovations, such as bug fixes, but does not decrease more substantial revisions. Additionally, it is associated with subsequent new product development. Managerial Abstract For many platform companies, a critical issue is understanding how piracy and imitation should be regulated, motivated in part by a common narrative that piracy will eliminate innovation on these platforms. The present article suggests that these effects are slightly more nuanced. We find that piracy does lead to a decline in incremental innovations, such as bug fixes or appearance tweaks, but no discernible decline in more major innovations, such as feature updates or entirely new versions. This implies that piracy can shape the type of innovation, potentially leading to products that are less polished and refined but not affecting the overall level of innovation.